The Influence of Influencers and Copywriting on Purchase Interest Mediated by Brand Awareness: Study of Scarlett Consumers in Malang - Dany Dwi Cahyo Prawiro; Fani Firmansyah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study seeks to analyze the impact of perceived value on repurchase intention among GoSend service users in Malang City. The study utilizes a quantitative methodology centered on analyzing customer behavior using explanatory research. The study population comprises consumers who have previously employed GoSend services. A sample size of 165 respondents was established using Malhotra's formula, selected by non-probability selection employing a purposive sampling strategy. Participants were mandated to have utilized GoSend services at least once and to dwell in Malang City. Data collection was executed by online surveys disseminated via links and QR codes. The questionnaire comprises indicators intended to assess perceived value, its constituents, and repurchase intention. Data analysis was conducted utilizing Structural Equation Modeling (SEM) with SmartPLS software to investigate the variables' correlations and validate the research model. The results indicate that perceived value substantially affects the repurchase intention of GoSend users. Elements influencing perceived value, including application incentives, perceived ubiquity, and visual appeal, were recognized as significantly and positively affecting users' decisions to utilize GoSend services regularly. Application incentives significantly enhance users' sense of value by providing tangible benefits that promote service loyalty. The perceived ubiquity, indicating the service's accessibility and simplicity, enhances users' favorable assessments of GoSend. The visual appeal of the application's design and interface enhances perceived value by delivering an intuitive and pleasurable user experience. These findings emphasize the significance of perceived value in affecting consumer loyalty and repurchase behavior. Service providers such as GoSend are urged to consistently improve elements that influence perceived value by providing competitive incentives, ensuring effortless access, and refining application design to align with changing user expectations. This research provides valuable information for digital service companies seeking to enhance their market presence and retain clients in a competitive landscape. Nonetheless, it recognizes constraints, including an exclusive emphasis on perceived value and its immediate constituents. Future research should investigate additional pertinent elements, including service reliability, user trust, and post-purchase assistance, to enhance the knowledge of the determinants of repurchase intention in digital services.